1
$\begingroup$

Is there a closed form for the infinite sum $$\sum \limits_{n=0}^{\infty} \frac{1}{(n+a)!} \mathrm{?}$$ where a is an integer greater than or equal to $0$.

When $a=0$, the sum is just the series expansion for $e$, $\sum \limits_{n=0}^{\infty} \frac{1}{n!}=e$

When $a=1$, the sum can be rewritten as $\sum \limits_{n=0}^{\infty} \frac{1}{(n+1)!}= \sum \limits_{n=1}^{\infty} \frac{1}{n!} =\frac{1}{1!}+\frac{1}{2!}+\frac{1}{3!}+ \dots=e-1$.

When $a=2$, the sum can be rewritten as $\sum \limits_{n=0}^{\infty} \frac{1}{(n+2)!}= \sum \limits_{n=2}^{\infty} \frac{1}{n!} =\frac{1}{2!}+\frac{1}{3!}+\frac{1}{4!}+\dots=e-2$.

When $a=3$, the sum can be rewritten as $\sum \limits_{n=0}^{\infty} \frac{1}{(n+3)!}= \sum \limits_{n=3}^{\infty} \frac{1}{n!} =\frac{1}{3!}+\frac{1}{4!}+\dots=e-\frac{5}{2}$.

$\vdots$

Thus, we can generalize that $$\sum \limits_{n=0}^{\infty} \frac{1}{(n+a)!}= \sum \limits_{n=a}^{\infty} \frac{1}{n!}.$$

Can this infinite sum be written in a closed form in terms of $a$? Following the pattern the general form would have some value, dependent on $a$, subtracted from $e$.

$\endgroup$
  • $\begingroup$ Can anyone explain why they voted to close this? $\endgroup$ – zz20s Feb 8 '16 at 13:03
  • $\begingroup$ This is the value of the Mittag Leffler function $E_{1,a+1}$ at $z = 1$. Other than that, it is just what you wrote it is - $e$ minus a finite sum. $\endgroup$ – Hans Engler Feb 8 '16 at 13:46
  • $\begingroup$ Right, my question is whether there exists a closed form for that finite sum. $\endgroup$ – zz20s Feb 8 '16 at 13:48
2
$\begingroup$

If you're familair with the gamma function:

$$\sum_{n=0}^{\infty}\frac{1}{(n+a)!}=\lim_{m\to\infty}\sum_{n=0}^{m}\frac{1}{(n+a)!}=$$ $$\lim_{m\to\infty}\frac{e\left(a!\Gamma(a+m+1,1)-a\Gamma(a,1)(a+m)!\right)}{a!(a+m)!}=$$ $$\frac{e}{a!}\lim_{m\to\infty}\frac{a!\Gamma(a+m+1,1)-a\Gamma(a,1)(a+m)!}{(a+m)!}=$$ $$\frac{e}{a!}\lim_{m\to\infty}\left(\frac{a!\Gamma(1+a+m,1)}{(a+m)!}-a\Gamma(a,1)\right)=$$ $$\frac{e}{a!}\left(\lim_{m\to\infty}\frac{a!\Gamma(1+a+m,1)}{(a+m)!}-a\Gamma(a,1)\right)=$$ $$\frac{e}{a!}\left(a!\lim_{m\to\infty}\frac{\Gamma(1+a+m,1)}{(a+m)!}-a\Gamma(a,1)\right)=$$ $$\frac{e}{a!}\left(a!\cdot1-a\Gamma(a,1)\right)=e-\frac{e\Gamma(a,1)}{\Gamma(a)}$$

$\endgroup$
1
$\begingroup$

Not clearly more convenient, but an alternative form can be built by first establishing that:

$$\int_0^1\frac{x^n}{n!}e^{-x}\,dx=1-\frac{1}{e}\sum_{k=0}^n\frac{1}{k!}$$

[This is best done by induction - if we call the integral on the left $I_n$, integrating by parts quickly gives us $I_n=I_{n-1}-\frac{1}{e\cdot n!}$.]

Noting that $\sum_{k=0}^{\infty}\frac{1}{k!}=e$, this can be recast as:

$$\int_0^1\frac{x^n}{n!}e^{-x}\,dx=\frac{1}{e}\sum_{k=n+1}^{\infty}\frac{1}{k!}$$

and shifting around the $n!$ and $e$ terms gives that

$$\sum_{n=a}^{\infty}\frac{1}{n!}=\int_0^1\frac{x^{a-1}}{(a-1)!}e^{1-x}\,dx$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.